A Forgotten Entity following Breast Implant Contracture: Does Baker Need a Change? - Andrea Pagani; Matthias M. Aitzetmüller; Lorenz Larcher (Archives of Plastic Surgery, 2022)
Although capsular contracture represents one of the most important complications after breast augmentation, local inflammation and fibrosis can lead, in very rare cases, to capsular calcification, an often-forgotten radiological sign of capsular contracture. In this article, the authors present a clinical case of breast implant calcification in an 81-year-old patient. Although this complication has been rarely described, the literature was reviewed to clarify the role of the local microenvironment in capsular contracture and calcification. At present, capsular contracture patients are classified using the conventional Baker score and the histological Wilflingseder classification. As it was not possible to consider capsular calcification when classifying our patient using the traditional scores, the authors propose an updated version of the current scale.